การศึกษาเปรียบเทียบของพอลิโพรพิลีนรีไซเคิลเทอร์มอพลาสติกวัลคาไนเซตจากยางธรรมชาติและจากยางอีพีดีเอ็ม - ทีปกร พันธ์พรม (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This study aimed to improve the properties of recycled PP by preparing thermoplastic elastomers (TPEs) and thermoplastic vulcanizate (TPVs) with natural rubber (STR5L) and EPDM at different ratios. The recycled PP/rubber blends with three ratios, including 90/10, 80/20, and 70/30 (w/w), were mixed in an internal mixer at 170 ºC for 10 mins, followed by compression molding. the results showed that the addition of either STR5L or EPDM rubber to the blends enhanced impact strength and elongation at break, but at the expense of the tensile strength, Young s modulus, and hardness. However, the TPEs by including EPDM exhibited superior properties than those including STR5L at the same ratio owing to the higher compatibility with recycled PP confirmed by morphological property. Among the TPEs, the recycled PP/rubber at 80/20 exhibited the appropriated mechanical properties. therefore, these ratio were chosen prepared TPVs by adding 1 and 2 phr of DCP as a crosslinking agent to examine and compare the mechanical, thermal, and morphological properties of the TPEs and TPVs. It was found that Young s modulus of the TPVs has higher than that of TPEs because of the crosslinking. However, other properties of the TPVs deteriorated as compared with the TPEs due to the chain scission by DCP.